Representation of a Minor in Civil Proceedings - Saneblidze, Mariam (European Scientific Journal, ESJ, 2026)
This article examines the legal and practical aspects of the representation of minors in civil proceedings, with particular emphasis on the principle of the best interests of the child as a fundamental standard of child protection. Due to their limited legal capacity and vulnerability, minors require enhanced legal safeguards, primarily ensured through the institution of legal representation. The representative plays a crucial role in guaranteeing the effective exercise of the child’s procedural rights and communicating the child’s views within judicial proceedings. The study analyzes international and domestic legal frameworks, including the United Nations Convention on the Rights of the Child and Georgian legislation, and demonstrates how the principle of the best interests of the child functions as a guiding standard in decision-making processes. A comparative perspective highlights differences in the application of this principle across legal systems, particularly regarding discretion and predictability. The article identifies key practical challenges, including the formalistic nature of representation, insufficient qualifications of representatives, and conflicts of interest between minors and their legal representatives. It also emphasizes the role of courts in ensuring that representation is not merely procedural, but genuinely effective. The findings suggest that effective representation depends not only on the existence of legal norms, but also on their proper implementation. Strengthening institutional mechanisms, improving professional training, and ensuring child-centered justice are essential for the effective protection of minors’ rights and the meaningful realization of the principle of the best interests of the child.